Salesforce behavioural performance of accounts relationship managers (ARMS) in Uganda ’ s commercial banks: A qualitative analysis - M. Ntayi, Joseph; Munene, John C.; Eyaa, Sarah (Journal of Retail & Leisure Property, 2010)
The purpose of this article is to examine the salesforce behavioural performance in commercial fi rms using a phenomenological approach. A sample of 75 accounts relationship managers (ARMS) from 15 commercial banks was selected. Results reveal that background factors provided vicarious reinforcement behaviours while vicarious punishment reinforced social skills that were necessary for selling bank services. Social network ties were particularly necessary in increasing salesforce behavioural performance while poor family background coupled with lack of career planning, limited professional sales presentation impacted negatively on the performance of the sales career. Serendipity, development networks, social dyadic interactions with customers and key stakeholders were found necessary in generating, building and retaining customers. This is because customers ’ lives depend on how they are tied into the larger web of social connections. We therefore recommend banks to hire ARMS based on vicarious learning, family background, social networking skills and development networks if they want to improve performance.
Keywords: Vicarious learning; Development networks; Serendipity; Sales career; Social networking